Heidegger's Being and time : a reader's guide - Blattner, William D., 1963- (Continuum reader's guides., 2006)
William Blattner explains the philosophical background against which the book was written and provides an overview of the key themes and motifs. He guides the reader to a clear understanding of Heidegger's work as a whole. He explores the reception and influence of the work and offers the student guidance on further reading.